Characteristic sediment and water column chlorophyll-a in the sea cucumber's Paracaudina sp. habitat on the Kenjeran Water, Surabaya. (March 2018) - Widianingsih, W; Zaenuri, M; Anggoro, S; Kusumaningrum, H P; Hartati, R
Abstract: The study of characteristic sediment and water column chlorophyll-a has an important role in the sea cucumber habitat. Sediment chlorophyll-a represents a productivity primer for the benthic community. This research has a purpose to investigate characteristic sediment and water column chlorophyll-a on the Kenjeran water, Surabaya. Sediment samples were collected by the ekman grab for analysis, grain size and nutrient. The sample for sediment chlorophyll-a was taken by core sampler. The water samples were taken with Nansen Bottles. According to the research result, the values of sediment chlorophyll-a at station 10, 11 and 12 were higher than the other stations. In contrast, the value of chlorophyll-a in the column water had almost the same value for each station. The sediment chlorophyll-a value on clay and silt sediment type was higher than the fine sand and coarse sediment type. The suitable habitat characteristic for Paracaudina sp. was clay and silt sediment with sediment chlorophyll concentration ranging from 347.82 mg·m -2 to 1135.52 mg·m -2 .